Aquatic plants as phytoindicator for heavy metals contaminant in polluted freshwater bodies - Othman, Rashidi; Hanifah, Nurul Azlen; Shaharuddin, Ruhul Izzati (Scientific Research Publishing Company, 2014)
Over the past decade, ecologists have tried to determine how changes in species composition and diversity affect ecosystem structure and function. Until recently, the majorities of these studies have been conducted in terrestrial ecosystems and have not taken into account environmental variability. Now a days, humans tend to neglect water as part of main sources in our daily life. As time goes by with few exceptions, water has always been a natural resource that people take for granted. The idea of this research is to understand how aquatic plants can be used to detect and act as an indicator for polluted freshwater bodies. In this study, sixteen water samples were collected from four different places (Selangor, Perak, Pahang and Kelantan) where six different aquatic plant species were abundance and dominant. All the water samples were analyzed for six types of heavy metals which are Iron (Fe), Lead (Pb), Copper (Cu), Zinc (Zn) and Nickel (Ni) and Manganese (Mn). All six different aquatic plant species which are Eichhornia crassipes, Hydrilla verticillata, Cabomba fuscata, Salvinia natans, Nelumbo nucifera and Pistia stratiotes exhibiting highly significant differences between aquatic plant species widespread, locations and the heavy metals content. This clearly demonstrates that freshwater environment with abundance of invasive macrophyte species can have an important influence and indication on the accumulation of heavy metals content. The importance of the interaction components emphasises that the changes in heavy metals composition are complex and the responses are not consistent across all aquatic plant species. Examination of the summarised data revealed that of the 6 macrophyte species analysed at all different locations, all exhibits as potential ecological indicator for unhealthy aquatic ecosystems or as phytoindicator for heavy metal contaminants either at low or high level contamination.